Effects of Special Pelvic Floor Muscle Training on the Quality of Life in Women with Urinary Incontinence, A Clinical Trial - Abbas Ali Pourmomeny; Anahita Torkzadeh; Mahtab Zargham (Shiraz University of Medical Sciences, 2018)
Background: Stress urinary incontinence (SUI) is the involuntary loss of urine which occurs with physical exertion and an increase in intra-abdominal pressure. Pelvic floor muscle training (PFMT) is generally recommended to reduce SUI. This study aimed to compare the effects of three different exercises in women with urinary incontinence by abdominal and pelvic floor muscle retraining. Methods: A total of 81 patients with urinary incontinence (UI) were randomly allocated to the pelvic muscle training by biofeedback (BF), pelvic muscle training by biofeedback plus abdominal exercise (BF+AbdExs), and only abdominal exercise (AbdExs). All participants received 12 weeks of treatment. The outcome measure was maximal vaginal squeeze pressure and Quality of life (QOL) Questionnaire. Data analysis was performed using ANOVA and Kruskal- Wallis tests. Results: The mean age of patients was 49.4±8.4 years. The scores of QOL, pelvic floor muscle strength, and endurance increased in all groups after the treatment. The mean score of QOL in group BF+Abd.Exs ranged from 65.2 to 93.6, while in groups BF and AbdExs, it ranged from 61.8 to 85.6 and 63.6 to 79.1 respectively. More aspects of QOL improved significantly in the BF+ AbdExs group than in other group. However, the difference in pelvic floor muscle strength and endurance was not statistically significant among the three groups (p>0.05) Conclusion: An increase in pelvic floor muscle strength was associated with AbdExs, which improved QOL. Thus, the AbdExs seems to induce cocontraction in pelvic floor exercise. However, AbdExs alone is not adequate for improving incontinence.